THE VALUE OF ENGLISH TECHNICAL LITERATURE IN AVIATION DEVELOPMENT - Bozarov, F.; Mamatov, F. (SCIENCE and SOCIETY, 2025)
The article highlights the role of English technical literature in aviation, aiding pilots, engineers, and researchers in deeply acquiring knowledge and understanding technical manuals. It emphasizes English as the global language of aviation, ensuring effective communication and knowledge transfer.